MiR-130a-3p Inhibits PRL Expression and Is Associated With Heat Stress-Induced PRL Reduction - Zhang, Haojie; Chen, Ting; Xiong, Jiali; Hu, Baoyu; Luo, Junyi; Xi, Qianyun; Jiang, Qingyang; Sun, Jiajie; Zhang, Yongliang (Frontiers in Endocrinology, 2020)
MicroRNAs (MiRNAs) play critical roles in the regulation of pituitary function. MiR-130a-3p has previously been found to be down-regulated in prolactinoma, but its roles in prolactin (PRL) regulation and the underlying mechanisms are still unclear. Heat stress has been shown to induce alteration of endocrine hormones and miRNAs expressions. However, there is limited information regarding the emerging roles of miRNAs in heat stress response. In this study, we transfected miR-130a-3p mimic into the pituitary adenoma cells (GH3 cells) to investigate the function of miR-130a-3p in regulating PRL. Our results showed that miR-130a-3p overexpression significantly decreased the PRL expression at both mRNA and protein levels. Subsequently, estrogen receptor α (ERα) was identified as a direct target of miR-130a-3p by bioinformatics prediction, luciferase reporter assay and western blotting assay. Furthermore, the inhibition of ERα caused by estrogen receptor antagonist significantly reduced the PRL expression. Overexpression of ERα rescued the suppressed expression of PRL caused by miR-130a-3p mimic. Besides, we also studied the effect of heat stress on PRL and miRNAs expressions. Interestingly, we found that heat stress reduced PRL and ERα expressions while it increased miR-130a-3p expression both in vitro and in vivo. Taken together, our results indicate that miR-130a-3p represses ERα by targeting its 3’UTR leading to a decrease in PRL expression, and miR-130a-3p is correlative with heat stress-induced PRL reduction, which provides a novel mechanism that miRNAs are involved in PRL regulation.